Strategi Public Relations PT Kasoem Hearing Dalam Mempublikasikan Kasoem Exhibition 2018 Kepada Masyarakat Indonesia - Mayasari, Silvina; Rahastine, Mareta Puri; Qibtiah, Annisa (Jurnal Komunikasi, 2019)
This final project aims to find out the strategies used in utilizing the digital world, in this case via Instagram and Facebook social media. Public Relations of PT.Kasoem Hearing uses Instagram and Facebook to publish the Exhibition 2018 Kasoem to customers and potential customers.The Kasoem Exhibition is a program to exhibit the entire series of hearing examinations,information on the habilitation stage after using a hearing aid and sharing stories of experiences with hearing aid users.The riset method used in this writing is a descriptive qualitative method where information obtained from direct observation techniques and in-depth interviews, then the results are stated in the form of research reports. PT.Kasoem Marketing Communications Manager PT. Becomes the guest speaker about the strategies carried out by the public relations team.The use of Instagram and Facebook is considered very effective in publishing an event. By uploading a series of events, promotions and grand prizes attract customers and prospective customers to know and participate in the event. This event was successful and can be seen from the number of visitors who attended more than the intended target. It can be concluded that Instagram social media and Facebook were able to become media to publish the 2018 Exhibition Casoem event.Keywords: PR Strategy, Publication, Social Media